Технология анализа согласованности и достоверности экспертных оценок - Лисецкий, Ю.М. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2017)
Приведены методы анализа экспертной информации. Предложена технология анализа экспертных оценок путем применения последовательности методов выявления неоднородности мнений экспертов, которая позволяет ускорить определение их согласованности и достоверности. Описан алгоритм реализации технологии. There are given methods of expert information analysis. There is proposed a technology to analyse expert opinions by means of application of the sequence of methods for discovery of the opinions’ heterogeneity. The technology accelerates determination of the opinions consistency and reliability. The algorithm of technology implementation is described.